An RNA Alternative to Human Transferrin: A New Tool for Targeting Human Cells - Samantha E Wilner; Brian Wengerter; Keith Maier; Maria de Lourdes Borba Magalhães; David Soriano Del Amo; Supriya Pai; Felipe Opazo; Silvio O Rizzoli; Amy Yan; Matthew Levy (Molecular Therapy: Nucleic Acids, 2012)
The transferrin receptor, CD71, is an attractive target for drug development because of its high expression on a number of cancer cell lines and the blood brain barrier. To generate serum-stabilized aptamers that recognize the human transferrin receptor, we have modified the traditional aptamer selection protocol by employing a functional selection step that enriches for RNA molecules which bind the target receptor and are internalized by cells. Selected aptamers were specific for the human receptor, rapidly endocytosed by cells and shared a common core structure. A minimized variant was found to compete with the natural ligand, transferrin, for receptor binding and cell uptake, but performed ~twofold better than it in competition experiments. Using this molecule, we generated aptamer-targeted siRNA-laden liposomes. Aptamer targeting enhanced both uptake and target gene knockdown in cells grown in culture when compared to nonmodified or nontargeted liposomes. The aptamer should prove useful as a surrogate for transferrin in many applications including cell imaging and targeted drug delivery.